Simulation of three-dimesional of coastal erosion using differential interferometric synthetic aperture radar - Marghany, Maged Mahmoud (Global NEST, 2014)
This study aims at modelling three-dimensional shoreline change rates using differential interferometric synthetic aperture radar (DInSAR) techinuqe. Neverthless, decorrelation plays significant role to control the accuracy of three dimensional object reconstruction using DInSAR. To solve this problem, multichannel MAP height estimator algorithm is implemented with in ENVISAT ASAR data. Therefore, the proposed method has been applied to coastaline of Johor, Malaysia. The study shows the critical erosion of -3.5 m y-1 with accuracy (RMSE) of ±0.05 m. In addition, the volume rate of shoreline changes of -2343.42 m3 y-1 corresponds to the lowest digital elevation model (DEM) of 7.4 m. It can be said that accurate rate of shoreline change can be achieved with root mean square error (RMSE) of ±0.05 m using multichannel MAP height estimator algorithm.